Disaggregating state fragility: a method to establish a multidimensional empirical typology - Grävingholt, Jörn; Ziaja, Sebastian; Kreibaum, Merle (Third world quarterly, 2015)
This conceptual and methodological article makes the case for a multidimensional empirical typology of state fragility. It presents a framework that defines fragile statehood as deficiencies in one or more of the core functions of the state: authority, capacity and legitimacy. Unlike available indices of state fragility, it suggests a route towards operationalisation that maintains this multidimensionality. The methodology presented should help in future research to identify clusters of countries that exhibit similar constellations of statehood, whereby ‘constellation’ refers to the specific mix of characteristics across the three dimensions. Such an identification of empirical types would fulfil a demand that exists both in academic research and among policy circles for finding a more realistic model of fragility at an intermediate level between single-case analyses and the far-too-broad category of state fragility.